U-rich elements drive pervasive cryptic splicing in 3’ UTR massively parallel reporter assays - Khoa Dao; Courtney F. Jungers; Sergej Djuranovic; Anthony M. Mustoe (Nature Communications)
Abstract Untranslated RNA sequences play essential roles in orchestrating gene expression. However, the sequence codes and mechanisms underpinning post-transcriptional regulation remain incompletely understood. Here, we revisit the finding from a prior massively parallel reporter assay (MPRA) that AU-rich elements in 3’ untranslated regions (3’ UTRs) can drive upregulation or downregulation of mRNA expression depending on 3’ UTR context. We unexpectedly discover that this variable regulation arises from widespread cryptic splicing, predominately from an unannotated splice donor in the coding sequence of GFP to diverse acceptor sites in reporter 3’ UTRs. Splicing is activated by U-rich sequences, which function as potent position-dependent regulators of 5’ and 3’ splice site choice and overall splicing efficiency. Splicing has diverse impacts on reporter expression, causing both increases and decreases in reporter expression via multiple mechanisms. We further provide evidence that cryptic splicing significantly impacts measurements made by other published 3’ UTR MPRAs. Overall, our work emphasizes U-rich sequences as principal drivers of splicing and provides strategies to minimize cryptic splicing artifacts in reporter assays.